Analysis Translation Methods of Text Translation in the Novel Al-Liṣ wa al-Kilāb by Najib Mahfuz - Ummi Choirun Nisa'; Imroatus Shalihah; Nur Qomari (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2023)
Based on Peter Newmark's translation methodology theory, this study aims to identify and classify the accuracy of the use of diction in the novel Al-Lis wa al-Kila>b. A descriptive qualitative approach was used in this research type. Reading techniques, document analysis, and sampling were used to collect data. Meanwhile, data is being analysed at the following stages: 1) identify and classify the original text based on the translation method, then compare the diction with the translated text, and 2) analyse and provide reasons for the translated text's incompatibility with the original text. The results showed that the most appropriate translation method to use in this novel is one that favours the target language, because translation methods that favour the source language have some diction inaccuracies. The original text's source language contains a style of language that cannot be interpreted lexically but must be interpreted contextually. The study's implication is to improve the reader's understanding of the author's intended message. مستخلص تهدف هذه الدراسة إلى تحديد وتصنيف دقة استخدام الإلقاء في رواية